A stereocontrolled synthesis of 3-acetamido-1,3,5-trideoxy- and 1,3,5,6-tetradeoxy-1,5-imino-D-glucitol - Simák, Ondrej; Stanek, Jan; Moravcová, Jitka (Carbohydrate research, 2009)
3-acetamido-5-amino-3,5,6-trideoxy-D-glucono-1,5-lactam and 3-acetamido-5-amino-3,5-dideoxy-D-glucono-1,5-lactam were synthesized from corresponding 3-acetamido-3-deoxy-beta-D-glucopyranosides in 63% and 35% overall yield, respectively. Acetylation followed by reduction led to the title 3-acetamido-3-deoxy derivatives of both deoxynojirimycin and 1,6-dideoxynojirimycin. The procedure developed is useful for a multi-gram scale.
Keywords: molekulární struktura; 1-Deoxynojirimycin; Molecular Structure; stereoizomerie; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Enzyme Inhibitors; inhibitory enzymů; Stereoisomerism; 1-deoxynojirimycin